An Implementation of Audio Security Using DES Algorithm - Abdul Wahid; Retantyo Wardoyo (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2007)
AbstractData security is an important problem in computer technology. This paper discusses security system for audio data. This technology is crucial because the multimedia technology has been improved very fast. One of the common audio format forms is wave audio format. The wave format is an uncompressed file format which is for RIFF specification owned by Microsoft. It is used for saving multimedia file. By using DES algorithm, the wave data could be encrypted for hiding information contained in the data. DES algorithm is chosen in this research because DES algorithm is one of the best symmetrical cryptography algorithms and it has been used world wide. This research is expected to give contribution to the audio security concept, especially for audio data security using wave file format.Keywords : audio security, DES algorithm, wave Omar